FORCED CONVECTION THERMAL BOUNDARY LAYER DEVELOPMENT IN A POROUS MEDIA NEAR A WALL WITH VARIABLE TEMPERATURE BOUNDARY CONDITION (Journal of Engineering, 2011)
The behavior of forced convection heat transfer characteristics through and over porous layer near aheated flat plate at variable temperature has been investigated numerically. Two cases of variable walltemperature boundary condition are studied. The first case is of linear temperature variation with positionalong the flat plate and the second case is of sinusoidal temperature variation with time of heating. The flow field in the porous region is governed by the Darcy-Brinkman-Forchheimer equation, the thermal field in the porous region by the energy equation and the part over the porous matrix includes flow and heat transfer equations. Solutions of the problem have been carried out using a finite difference method through the use of a stream function-vorticity transformation. The effects of various governing dimensionless parameters, Darcy number, Reynolds number, Prandtle number as well as the inertia parameter are thoroughly explored. The variation of the non-dimensional period and amplitude values of the sinusoidal temperature distinction with time was also studied. Good results were obtained and reported graphically. It was found that the local Nusselt number on the flat plate increases with the increasing of the increasing non-dimensional values of period and amplitude individually.